Principles and applications of soil microbiology - Gentry, Terry J.; Fuhrmann, Jeffry J.; Zuberer, David A. (Elsevier, 2021)
Written by leading experts in their respective fields, Principles and Applications of Soil Microbiology 3e, provides a comprehensive, balanced introduction to soil microbiology, and captures the rapid advances in the field such as recent discoveries regarding habitats and organisms, microbially mediated transformations, and applied environmental topics. Carefully edited for ease of reading, it aids users by providing an excellent multi-authored reference, the type of book that is continually used in the field. Background information is provided in the first part of the book for ease of comprehension. The following chapters then describe such fundamental topics as soil environment and microbial processes, microbial groups and their interactions, and thoroughly addresses critical nutrient cycles and important environmental and agricultural applications. An excellent textbook and desk reference, Principles and Applications of Soil Microbiology, 3e, provides readers with broad, foundational coverage of the vast array of microorganisms that live in soil and the major biogeochemical processes they control. Soil scientists, environmental scientists, and others, including soil health and conservation specialists, will find this material invaluable for understanding the amazingly diverse world of soil microbiology, managing agricultural and environmental systems, and formulating environmental policy.